Social Media Regulation: The Impact on Freedom of Expression - Zubaida Zafar; Shoukat Ali (International Journal of Law and Political Authority, 2026)
The rapid expansion of social media has transformed freedom of expression from a predominantly state-regulated right into a practice mediated by complex regulatory and platform-based governance structures. This study examines how social media regulation influences the scope, exercise, and substance of freedom of expression within contemporary digital environments. Employing normative legal analysis supported by comparative and empirical insights, the research explores the interaction between statutory regulation, administrative enforcement, and private content moderation. The findings demonstrate that regulatory mechanisms addressing misinformation, hate speech, and digital risk often generate indirect constraints on lawful expression through uncertainty, self-censorship, and privatized enforcement practices. Empirical evidence from prior studies and official assessments indicates that these effects extend to democratic discourse, political participation, and expressive autonomy across different jurisdictions. The study argues that social media regulation has not eliminated freedom of expression, but has reconfigured its operation by embedding it within multilayered governance systems. Understanding this transformation is essential for evaluating the legitimacy and democratic consequences of contemporary regulatory approaches to online expression..